Perspectives of the System's Professional Military Education Development in the Context of the World's Experience - Mandragelja, Volodymyr (Filosofiya osvity. Philosophy of Education, 2008)
The changes that take place in the structure, objects and role of the armed forces, its influence on the system of professional military education have been analyzed in the paper. The essence and content of the competency map, positive and negative aspects of the military specialists' preparation have been examined. Limited of the detailed formalization of traits and attributes of military leaders that will be urgency in the future is grounded. The necessity of the system approach to military preparing, that includes working conditions, stimulus and motivation besides competency is emphasized.